ANALYSIS OF FUND RAISING IN ISLAMIC BANKS IN THE NEW NORMAL ERA - Aulia Rahman (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study, to see the model of fundraising carried out by financial institutions in the current New Normal era.The outbreak of the Covid 19 virus in Indonesia has disrupted all operational systems, one of which is the operational system of Islamic financial institutions.Islamic financial institutions have an obligation to collect and channel funds to the public, but because of the spread of the covid 19 virus, all activities are carried out remotely.To continue to carry out the obligations of Islamic financial institutions, as financial institutions, Islamic financial institutions create a method that can carry out their functions.This research is a qualitative research, in which later researchers will conduct interviews with several Islamic financial institutions, regarding the methods of raising funds by Islamic financial institutions in the current new normal era, in order to continue to carry out the functions of Islamic financial institutions.Keywords: Funds Collection Model, Islamic Bank, New Normal